Generalized weighted statistical convergence of double sequences and applications - Cinar, M.; E,t M. (University of Nis, 2016)
In this paper we introduce the concept generalized weighted statistical convergence of double sequences. Somerelations between weighted (?, ?)- statistical convergence and strong (N??p, q, ?, ?)- summablity of double sequences are examined. Furthemore, we apply our new summability method to prove a Korovkin type theorem. © 2016, University of Nis. All rights reserved.
Keywords: Double sequences; Korovkin type theorem; Weighted statistical convergence